Placenta and placental barrier. - Purizaca Benites, Manuel (2015)
We present an update on placental physiology and placenta as a barrier, from maternal uterus modifications- a process known as decidualization, implantation and trophoblast invasion, until the placental barrier is established; we explain the different mechanisms of mother-child transfer with emphasis in the transport molecules. Finally we recall the relationship between pregnancy and inflammation as determined by cytokine expression profile and summarize the trophoblast endocrine function.